Planning for the Development of Pantai Utara of Kabupaten Manokwari (Study on Nuni Beach) as a Tourism Area - Murni, Murni; Abubakar, Endang; Rumbarar, Samuel (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
The sustainability of the tourism area can be realized if there is a balance between aspects in the development area, so that the area is able to show the functionality between each aspect in the development area. The analysis methods in this study are qualitative analysis, site analysis, and SWOT analysis. The results of this study are (a) The development of the Nuni Beach tourism area is planned with a clear division of zones, namely the Public Zone, Semi-Private Zone, and Private Zone, to facilitate accessibility and comfort for visitors and managers. The total area of the planned area reaches ± 71,249.3 m², including various facilities such as parking areas, management offices, accommodation, multi-purpose rooms, as well as places to eat and parks. This approach is expected to support the growth of planned and sustainable tourism in Nuni Beach, while maintaining environmental sustainability and providing a pleasant experience for tourists; and (b) The development strategy of Nuni Beach as a tourism area focuses on utilizing existing strengths and opportunities through an aggressive approach, while overcoming weaknesses and threats with comprehensive planning. Through effective promotion, infrastructure improvement, human resource training, and sustainable environmental management, it is hoped that Nuni Beach can develop into an attractive and sustainable tourist destination, attracting more tourists while preserving nature.